Mouse embryonic fibroblasts expressing IFNβ or IL-21 inhibit proliferation of melanoma cells in vitro - Vagyna, I.N.; Zaharuk, O.A.; Strokovska, L.I.; Vagyn, Y.V.; Kashuba, V.I. (Вiopolymers and Cell, 2016)
Aim. To study an influence of mouse embryonic fibroblasts (C57Fb) transduced with baculovirus vectors (BVs), encoding genes for murine Ifn-β or human IL21, on survival and proliferation of the malignant mouse melanoma cells (B16) in vitro. Methods. Transduction of cells, construction of BVs, RNA isolation, quantitative PCR. Results. We have shown that the normal C57Fb and B16 tumor cells are sensitive to the anti-proliferative effect of IFNβ. Rapidly proliferating B16 cells were the most sensitive. BV ensured a stable expression of Ifnβ mRNA for 5 days in C57Fb/IFNβ cells. The growth of B16 cells was suppressed upon co-cultivation with C57Fb/IFNβ or C57Fb/IL21 cells. Conclusions. IFNβ and IL-21 synthesized by the mouse embryonic fibroblasts transduced with BVs carrying the Ifnβ or IL-21genes inhibited proliferation of B16 melanoma cells in vitro.